Revisiting the Link between Growth and Federalism: A Bayesian Model Averaging Approach - Zareh Asatryan; Lars P. Feld (Center for Economic Studies and ifo Institute (CESifo), 2013)
Following the ambiguous results in the literature aimed at understanding the empirical link between fiscal federalism and economic growth, this paper revisits the question using a Bayesian Model Averaging approach. The analysis suggests that the failure to appropriately account for model uncertainty may have previously led to biased estimates. The results from a sample of 23 OECD countries over 1975-2000 indicate that after controlling for unobserved country heterogeneity, there is no robust link, neither positive, nor negative, between output growth and fiscal federalism (measured as sub-national governments' share of own source tax revenue).
Keywords: C11; H70; O43; 330; fiscal federalism; economic growth; Bayesian Model Averaging